2012
DOI: 10.1124/dmd.112.046748
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Pregnane X Receptor (PXR) Function andUGT1A1Gene Expression by Posttranslational Modification of PXR Protein

Abstract: ABSTRACT:Human UDP-glucuronosyltransferase (UGT) 1A1 is a critical enzyme responsible for detoxification and metabolism of endogenous and exogenous lipophilic compounds such as bilirubin. The present study shows how cyclin-dependent kinase (CDK) inhibitor roscovitine stimulated the expression of UGT1A1 in HepG2 cells. Pregnane X receptor (PXR)-mediated transactivation of UGT1A1 reporter gene was more prominently enhanced by roscovitine, compared with the basal-, constitutive androstane receptor (CAR)-, and ary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 35 publications
(56 reference statements)
2
51
0
Order By: Relevance
“…In a previous study (Sugatani et al, 2012), we found that the expression of UGT1A1 induced by the CDK2 inhibitor roscovitine was increased in HepG2 cells in the presence of exogenously expressed hPXR, whereas a phosphomimetic mutation at the threonine-57, threonine-290, serine-350, and threonine-408 of hPXR suppressed the activity induced by roscovitine. The phosphomimetic T290D mutant YFP-hPXR fusion protein but not the S350D or T408D mutant proteins was markedly retained in the cytoplasm and suppressed nuclear translocation after the treatment with roscovitine (Sugatani et al, 2012).…”
Section: Effects Of Phosphomimetic and Phosphodeficient Mutations Atmentioning
confidence: 74%
See 4 more Smart Citations
“…In a previous study (Sugatani et al, 2012), we found that the expression of UGT1A1 induced by the CDK2 inhibitor roscovitine was increased in HepG2 cells in the presence of exogenously expressed hPXR, whereas a phosphomimetic mutation at the threonine-57, threonine-290, serine-350, and threonine-408 of hPXR suppressed the activity induced by roscovitine. The phosphomimetic T290D mutant YFP-hPXR fusion protein but not the S350D or T408D mutant proteins was markedly retained in the cytoplasm and suppressed nuclear translocation after the treatment with roscovitine (Sugatani et al, 2012).…”
Section: Effects Of Phosphomimetic and Phosphodeficient Mutations Atmentioning
confidence: 74%
“…Thus, in the present study, CYP3A4 and UGT1A1 were used as biomarkers of exogenously expressed hPXR activation. In a previous study (Sugatani et al, 2012), we demonstrated that a phosphomimetic mutation at the threonine-290 of hPXR suppressed the ligand-independent translocation of hPXR to the nucleus. We herein identified a phosphomimetic mutant of hPXR that abrogated ligand-induced nuclear translocation.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations